Factor VIIa binding to endothelial cell protein C receptor: Differences between mouse and human systems - Sen, Prosenjit; Clark, Curtis A.; Gopalakrishnan, Ramakrishnan; Hedner, Ulla; Esmon, Charles T.; Pendurthi, Usha R.; Rao, L. Vijaya Mohan (Thrombosis and Haemostasis, 2012)
Recent in vitro studies have shown that the zymogen and activated form of factor (F)VII bind to endothelial cell protein C receptor (EPCR). At present, there is no evidence that FVIIa binds to EPCR on vascular endothelium in vivo in the presence of circulating protein C, a primary ligand for EPCR. The present study was carried out to investigate the interaction of murine and human ligands with murine EPCR both in vivo and in vitro. Measurement of endogenous plasma levels of FVII in wild-type, EPCR-deficient and EPCR-over expressing mice showed slightly lower levels of FVII in EPCR-over expressing mice. However, infusion of high concentrations of competing ligands, either human APCi or FVIIai, to EPCR-over expressing mice failed to increase plasma levels of mouse FVII whereas they increased the plasma levels of protein C by two- to three-fold. Examining the association of exogenously administered mouse FVIIa or human FVIIa by immunohistochemistry revealed that human, but not murine FVIIa, binds to the murine endothelium in an EPCR-dependent manner. In vitro binding studies performed using surface plasmon resonance and endothelial cells revealed that murine FVIIa binds murine EPCR negligibly. Human FVIIa binding to EPCR, particularly to mouse EPCR, is markedly enhanced by availability of Mg2+ ions. In summary, our data show that murine FVIIa binds poorly to murine EPCR, whereas human FVIIa binds efficiently to both murine and human EPCR. Our data suggest that one should consider the use of human FVIIa in mouse models to investigate the significance of FVIIa and EPCR interaction.
Keywords: Endothelial cell protein C receptor; factor VIIa; protein C